2019
DOI: 10.1097/md.0000000000015248
|View full text |Cite
|
Sign up to set email alerts
|

Oral vs intravenous tranexamic acid in total-knee arthroplasty and total hip arthroplasty

Abstract: Background: This study aimed to compare the efficacy and safety of oral tranexamic acid (TXA) with intravenous (IV) TXA in reducing perioperative blood loss in total-knee arthroplasty (TKA) and total-hip arthroplasty (THA). Methods: PubMed, Web of Science, Embase, and Cochrane Library were fully searched for relevant studies. Studies comparing the efficacy and safety of oral TXA with IV TXA in TKA and THA were included in this research. Odds ratio (OR) or risk differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…At present, a large number of studies report that TXA is safe and effective in hip and knee joint replacement, regardless of the mode of administration, intravenous, topical, or combination [12][13][14][15]. However, no study has reported on the intravenous infusion of TXA in the acetabulum in terms of its effect on blood loss during the perioperative period in these fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, a large number of studies report that TXA is safe and effective in hip and knee joint replacement, regardless of the mode of administration, intravenous, topical, or combination [12][13][14][15]. However, no study has reported on the intravenous infusion of TXA in the acetabulum in terms of its effect on blood loss during the perioperative period in these fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of intravenous use of TXA TXA is a synthetic lysine analog that inhibits brinolytic activity by competitively inhibiting the binding of plasminogen to brin, thereby inhibiting brinolysis and reducing perioperative blood loss. Chen et al [12] conducted a meta-analysis using TXA in TKA and THA, and concluded that intravenous use of TXA can reduce perioperative blood loss, which is worthy of clinical recommendation. A multicenter retrospective study on simultaneous bilateral knee replacement surgery reported that intravenous use of TXA is safe and effective, and reduces perioperative blood loss without increasing complications [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a large number of studies report that TXA is safe and effective in hip and knee joint replacement, regardless of the mode of administration, intravenous, topical, or combination [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of intravenous use of TXA TXA is a synthetic lysine analog that inhibits fibrinolytic activity by competitively inhibiting the binding of plasminogen to fibrin, thereby inhibiting fibrinolysis and reducing perioperative blood loss. Chen et al [11] conducted a meta-analysis using TXA in TKA and THA, and concluded that intravenous use of TXA can reduce perioperative blood loss, which is worthy of clinical recommendation. A multicenter retrospective study on simultaneous bilateral knee replacement surgery reported that intravenous use of TXA is safe and effective, and reduces perioperative blood loss without increasing complications [15].…”
Section: Discussionmentioning
confidence: 99%